Experimental and numerical study on global buckling of Q460GJ steel box columns under eccentric compression. (1st July 2017) - Nie, Shi-Dong; Kang, Shao-Bo; Shen, Le; Yang, Bo
Highlights: Experimental tests were conducted on welded Q460GJ steel box columns under axial compression and bending moment. Numerical models were developed to simulate the global buckling behaviour of steel columns subject to eccentric compression, in which geometric imperfections and residual stresses were considered. Design recommendations were proposed for global buckling design of Q460GJ steel box columns under eccentric compression. Abstract: This paper describes an experimental and numerical study on the global buckling behaviour of welded Q460GJ steel box columns subject to eccentric compression. Eight box columns with various cross sections, slendernesses and eccentricities were tested in the experimental programme. All columns exhibited global buckling with significant lateral deflections. Comparisons were made between test data and design values calculated from different design codes. Besides, numerical models were developed in which initial geometric imperfections and residual stresses were considered. The model was verified by experimental results and reasonably good agreement was obtained between numerical and experimental results. Parametric study was conducted on the effects of slenderness and eccentricity ratio on the load capacity of box columns. Finally, design recommendations were made based on the comparisons between numerical results and design curves in different codes. It was suggested that curve "a" in GB50017-2003 and curve "c" in Eurocode 3 are appropriate for the global buckling design of welded Q460GJ steel box columns under eccentric compression. Design curves in ANSI/AISC360-10 and AIJ 2010 also provides good predictions of the load capacity.